Assessing the salinization mechanisms of coastal brackish springs - Sanz, Esteban; Carrera, Jesús; Ayora, Carlos; Barón, Alfredo; González, Concha (Comptes Rendus. Géoscience)
Brackish springs have been extensively reported in Mediterranean coastal carbonate formations. The phenomenon is puzzling because these springs may discharge high flow rates with significant salinities at elevations of several meters above sea level. Although these springs have been studied for millennia (since the ancient Greeks), controversy persists. In essence, they are typically assumed to consist of a karstic conduit bringing fresh groundwater that meets a saltwater conduit at a branching point, where the brackish mixture flows up to the spring mouth. Here, we analyze the hydraulics of the system for two simple cases, depending on whether seawater flow occurs through an open conduit or a porous aquifer. To this end, we derive the equations governing variable-density turbulent flow through the conduits. These turn out to be similar to the traditional ones, except that (1) Bernouilli’s head (energy per unit weight) is substituted by the energy per unit volume, and (2) this energy is not a potential, as a flow path dependent term needs to be added. We solve these equations to obtain the characteristic functions relating fresh to seawater discharge depending on spring concentration. These functions are specific to every brackish spring and representative of the karst system and salinization mechanism. They allow us to show that the spring salinity is mostly controlled by the weight of the water column flowing towards the spring mouth (for low flow rates) and by energy dissipation (for high flow rates). When concentration and flow rate data are available, it is possible to characterize: (1) the resistance of the upwards conduit from the response at high flow rate; (2) the depth of the branching point from the concentration at low discharges; and (3) the hydraulic resistance of the seawater conduit from the slope of concentration vs. flow rate at low spring discharges. These patterns are compared to field data from three different springs, which yields insights on the conceptual model governing every particular spring.